2009
DOI: 10.3390/v1030545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type-I Interferon on Retroviruses

Abstract: Type-I interferons (IFN-I) play an important role in the innate immune response to several retroviruses. They seem to be effective in controlling the in vivo infection, though many of the clinical signs of retroviral infection may be due to their continual presence which over-stimulates the immune system and activates apoptosis. IFN-I not only affect the immune system, but also operate directly on virus replication. Most data suggest that the in vitro treatment with IFN-I of retrovirus infected cells inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 146 publications
(221 reference statements)
0
17
1
Order By: Relevance
“…While most MS patients are phenotypically RRMS, it remains to be addressed whether the same finding between MSRV DNA copy number and vitamin D level is found with other types of MS such as primary progressive multiple sclerosis (PPMS). Although it has been indicated that type I IFNs affect the terminal stages of the retroviral cycle, the present cross sectional study cannot rule out a potential influence of treatment on MSRV DNA copy numbers in these patients due to the small number of patients with each type of therapy, the type of interferon and its dosage, differences in treatment duration between patients, and lack of drug naïve patients.…”
Section: Discussionmentioning
confidence: 71%
“…While most MS patients are phenotypically RRMS, it remains to be addressed whether the same finding between MSRV DNA copy number and vitamin D level is found with other types of MS such as primary progressive multiple sclerosis (PPMS). Although it has been indicated that type I IFNs affect the terminal stages of the retroviral cycle, the present cross sectional study cannot rule out a potential influence of treatment on MSRV DNA copy numbers in these patients due to the small number of patients with each type of therapy, the type of interferon and its dosage, differences in treatment duration between patients, and lack of drug naïve patients.…”
Section: Discussionmentioning
confidence: 71%
“…The in vitro effects of IFN-I on human retroviruses have been extensively studied. Generally, results from most studies have shown that retroviral protein synthesis is not affected, and suggest that IFN affects the latter stages of the viral cycle, preventing correct assembly or the release of viral particles (review in Gómez-Lucía et al, 2009). Unfortunately, few studies have focused on the effect of this cytokine on feline retroviruses (Rogers et al, 1972;Jameson and Essex, 1983;Yamamoto et al, 1986;Tanabe and Yamamoto, 2001;Collado et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…107,109 Thereby IFNs prevent the spread of virus from infected cells and aid in the clearance of virus infection. 107 Human IFNs have been manufactured by recombinant DNA technology and are available commercially.…”
mentioning
confidence: 99%